Activation of basolateral amygdala to anterior cingulate cortex circuit alleviates MK-801 induced social and cognitive deficits of schizophrenia - Huang, Xin; Li, Yaohao; Liu, Haiying; Xu, Jinwei; Tan, Zehua; Dong, Haoyang; Tian, Biqing; Wu, Shengxi; Wang, Wenting (Frontiers in Cellular Neuroscience, 2022)
Although schizophrenia is a severe psychiatric disorder with a high prevalence worldwide, its pathogenesis remains poorly understood. In this study, we used the noncompetitive NMDA receptor antagonist MK-801 to induce schizophrenia-like behaviors and confirmed that mice exhibited stereotypic rotational behavior and hyperlocomotion, social interaction defects and cognitive dysfunction, similar to the clinical symptoms in patients. Here, the anterior cingulate cortex (ACC) and basolateral amygdala (BLA) were involved in the schizophrenia-like behaviors induced by MK-801. Furthermore, we confirmed BLA sent glutamatergic projection to the ACC. Chemogenetic and optogenetic regulation of BLA-ACC projecting neurons affected social and cognitive deficits but not stereotypic rotational behavior in MK-801-treated mice. Overall, our study revealed that the BLA-ACC circuit plays a major role and may be a potential target for treating schizophrenia-related symptoms.